Sobrevivencia de cultivos pansensibles de Mycobacterium tuberculosis a Isoniacida y Rifampicina y su relación con parámetros epidemiológicos. Macro Región Norte, Chiclayo 2011 - Ventura Flores, Roberto (2013)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, where a third of the world's population is infected and nearly two million die from the disease. In Peru each year are affected between 35,000 to 50,000 people, being timely diagnosis vital to the initiation of treatment. The objective was to identify pansusceptible cultures and profile of resistance of Mycobacterium tuberculosis of the Macro Region Norte and determine the survival of pansusceptible cultures of M. tuberculosis to isoniazid and rifampicina and relationship with parameters epidemiological. The susceptibility of M. tuberculosis to first-line drugs was determined using method of proportions (Canetti, 1963) in solid medium of Lowenstein Jensen with Isoniazid (H), rifampicin (R), Streptomycin (S) and Ethambutol (E), the susceptibility to pyrazinamide was determined with the pyrazinamidase test (Wayne, 1974). The survival of pansusceptible cultures of Mycobacterium tuberculosis to isoniazid and rifampicin was carried out in a drug-free Ogawa medium by a method adapted in the area of mycobacteria at the Chiclayo Referential Laboratory. 1141 cultures were analyzed by susceptibility testing, of which 13.1%, 4.2%, 1.7%, 0.7% and 0.4% respectively were resistant to one; two, three, four and five antituberculosis drugs also detected 912 (79.9%) pansusceptible cultures. Of 202 pansusceptible cultures was found a survival of 50 (24.75%), of these 12 were to isoniazida, 34 to rifampicin and 4 to both drugs.